2023
DOI: 10.1155/2023/9889533
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-Hydroxy-β-Methylbutyrate Supplementation Affects Growth Performance, Digestion, TOR Pathway, and Muscle Quality in Kuruma Shrimp (Marsupenaeus japonicas) Fed a Low Protein Diet

Abstract: An 8-week feeding trial was performed to evaluate the effects of dietary β-hydroxy-β-methylbutyrate (HMB) supplementation on growth performance and muscle quality of kuruma shrimp (Marsupenaeus japonicas) (initial weight: 2.00 ± 0.01   g ) fed a low protein diet. The positive control diet (HP) with 490 g/kg protein and negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…The shrimp meat in the control group showed a significantly (p < 0.05) higher value of WBS as compared to the groups in which fishmeal was replaced. Mu et al [50] noted in aquatic animals a negative correlation between muscle texture and fat content; in this study, softer meat was found in the fishmeal replacement groups, which contained a higher amount of fat as compared to the control group. Dunajski [51] stated that the shrimps' muscle texture depended on the connective tissue and the integrity of myofibrillar proteins, which can change when the protein concentration in feed is modified [52].…”
Section: Muscle Quality Parameterssupporting
confidence: 53%
“…The shrimp meat in the control group showed a significantly (p < 0.05) higher value of WBS as compared to the groups in which fishmeal was replaced. Mu et al [50] noted in aquatic animals a negative correlation between muscle texture and fat content; in this study, softer meat was found in the fishmeal replacement groups, which contained a higher amount of fat as compared to the control group. Dunajski [51] stated that the shrimps' muscle texture depended on the connective tissue and the integrity of myofibrillar proteins, which can change when the protein concentration in feed is modified [52].…”
Section: Muscle Quality Parameterssupporting
confidence: 53%
“…Notably, there was a study reporting that the serum total amounts of EAA and NEAA in the serum of pigs were unaffected by dietary HMB supplementation ( Zheng et al, 2021 ). In addition, increasing the dietary levels of HMB (0.025–0.20%) did not affect the Asp content while increased the contents of the Glu and total EAA in muscle ( Mu et al, 2023 ). It seems that the results mentioned in the previous studies are contrary to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the IMF content, recent evidence from growing pigs and Kuruma Shrimp has also shown that dietary HMB supplementation can regulate the muscular compositions of free amino acids and fatty acids ( Zhong et al, 2019 ; Mu et al, 2023 ). Both the contents of IMF and free amino acids are the crucial factors that contribute to the taste of meat ( Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In grass carp, muscle hardness is influenced by the dietary protein level, which affects the growth of muscle fibers as well as the synthesis and degradation of collagen [2]. In kuruma shrimp, a low dietary protein level has been shown to slow down the growth rate, decrease the intestinal trypsin activity, and affect the hardness [3]. Furthermore, studies have indicated that a 45% protein dietary was more susceptible to oxidative stress than the 55% protein dietary group for Senegalese sole juveniles (Solea senegalensis) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Animals need to accelerate the formation of ATP to replenish energy due to enhanced protein metabolism, and the amount of ROS, a by-product of ATP formation, increases significantly, inducing oxidative damage. Recent findings in grass carp reveal that diets with different protein levels regulate antioxidant capacity and improve muscle texture and flavor, primarily by regulating the muscle Nrf2-Keap1 signaling pathway, which mediates antioxidant enzyme activity and gene expression [3]. Autophagy is inextricably linked to oxidation, and since autophagy is an organism's response behavior to mitigate oxidative stress, its level might also change depending on the degree of oxidative damage in the organism.…”
Section: Introductionmentioning
confidence: 99%